Treatment outcome of tuberculosis patient of Samtse General Hospital, Bhutan (Nepal Journal of Epidemiology, 2020)
Background: Tuberculosis (TB) is one of the major public health problems in Bhutan. Evaluation of treatment outcomes of TB and identification of the risk factors are important components for the success of National TB control program. Therefore, this study was undertaken to assess the TB treatment outcome and factors associated with it in Samtse General Hospital.Methods: This was a retrospective, cross sectional study using the TB data from Samtse General Hospital from 2008–2019. A univariate and multiple logistic regression was used to check for associations between the outcome and other independent variables.Results: The study included a total of 634 TB patients. Of this, 44.0% (279) were smear positive TB (PTB+), 36.1% (229) were extra pulmonary TB (EPTB) and 19.9% (126) were smear negative TB (PTB-). During the study period, 56.2% (356) of them completed treatment, 33.3% (211) were declared cured, 0.2% (1) had defaulted, 5.1% (32) died and 5.4% (34) had treatment failure. The mean treatment success rate (TSR) was 89.4% (567). The TSR was highest for EPTB with 96.9% (222/229), followed by PTB- at 88.1% (111/126) and lowest for PTB+ with 83.9% (234/279). Successful treatment outcome was observed in EPTB patients (AOR: 7.3; 95% CI: 2.46-21.36), patients in age 15-28 years (AOR: 3.4; 95% CI: 1.59-7.46) and 29-42 years (AOR: 9.1; 95% CI: 2.44-33.61).Conclusion: The treatment outcome of TB in Samtse General Hospital is satisfactory and at par with the national level. Since, smear positive TB and elderly patients are prone to develop poor treatment outcome, they need to be monitored and followed up adequately.